IDENTIFIKASI MORFOLOGI dan PARAMETER SPESIFIK SIMPLISIA DAN EKSTRAK DAUN ROSELLA (Hibiscus sabdariffa L.) ASAL KAB. ENREKANG (SULAWESI SELATAN) - A. Amalia Dahlia; Asni Amin; Rahayu Lestari (As-Syifaa Jurnal Farmasi, 2012)
Identification of morphology and spesific parameters from simplicia and rosella leaf's extract (Hibiscus sabdariffa L.). From regency of Enrekang, South Sulawesi. Identification of morphology and spesific parameters from simplicia and rosella leaf's extract have been done. The aim of this research is to know morphology and to get data of spesific parameters from simplicia and rosella leaf's extract (Hibiscus sabdariffa L.). Morphology test showed that rosella leaf's had spesific characteristic, i.e had red nervatio, had three palmatifidus leaf and their edge of leaf was serrated. Microscopic test of simplicia showed that the shape of their xilem was spiral and ladder, mesophyl, had thick trachoma, Ca.oksalat shaped sand, fibers sklerenkim, oil cells, epidermis and, diasitik stomata type, cortical parenchyma and lymph lysogen. Chemical identification of rosella leaf's powder showed that lignin, cathecol, aleuron, and flavanoid. Spesific parameters of extract showed that water soluble compound was 6,6203% and ethanol soluble acompund was 18,6992%. Identification of chemical group used Thin Layer Chromatography that sprayed by spesific reagent showed that the extract contained terpenoid and flavonoid.Key word : Identification, morphology, Hibiscus sabdariffa L